Nanoimprinted ultrafine line and space nanogratings for liquid crystal alignment - Leong, Eunice Sok Ping (2013)
Ultrafine 50 nm line and space nanogratings were fabricated using nanoimprint lithography, and were further used as an alignment layer for liquid crystals. The surface morphologies of the nanogratings were characterized and their surface energies were estimated through the measurement of the contact angles for two different liquids. Experimental results show that the surface energies of the nanogratings are anisotropic: the surface free energy towards the direction parallel to the grating lines is higher than that in the direction perpendicular to the grating lines. Electro-optical characteristics were tested from a twisted nematic liquid crystal cell, which was assembled using two identical nanogratings. Experimental results show that such a kind of nanograting is promising as an alternative to the conventional rubbing process for liquid crystal alignment.